Protecting source–location privacy based on multirings in wireless sensor networks. (21st June 2013) - Yao, Lin; Kang, Lin; Deng, Fangyu; Deng, Jing; Wu, Guowei; Orgun, Mehmet A.; Orgun, Atilla Elçi; Pieprzyk, Josef; Chefranov, Alexander; Shankaran, Rajan; Wang, Huaxiong; Zhuge, Hai
Summary Wireless sensor networks (WSNs) are expected to be widely deployed to collect data in military and civilian applications. Because of the open nature of WSNs, it is easy for an adversary to eavesdrop sensor communication and to trace packets, causing privacy concern for the sensor devices. The privacy issue, especially location privacy, can be critical for monitoring applications in WSNs. A unique case of location privacy is that of the sources, which are vulnerable of being captured and target attacks. In this paper, we propose a scheme to protect the source–location privacy based on a novel use of multiring topology. To achieve a uniformly distributed traffic pattern throughout the network, the source node selects two random rings each from its external rings and internal rings and a set of two random angles with a sum of 180 degrees for each packet. The packet is sent at one of the angles in each ring. Fake packets are also injected to provide path diversity and to increase attack time, which is defined as the time that the adversary takes to locate the source successfully. These techniques protect the source node from packet tracing attacks as well as traffic analysis attacks. Our analysis and simulations, performed in the NS2 simulator and MATLAB, demonstrate that our proposed scheme can provide better spatial traffic evenness and longer attack time, along with a modest increase of hop count and energy consumption.Copyright © 2013 John Wiley & Sons, Ltd.